Chronic folliculitis of the scalp: New classification of one spectrum related variants - Sharquie, Khalifa E.; Jabbar, Raed I. (Journal of Pakistan Association of Dermatologists, 2022)
Background Chronic scalp folliculitis is a chronic inflammatory process of hair follicles that results from a change in the microbiome of hair follicles rather than actual pathogenic microbial infection. Objective To gather all cases that present with chronic folliculitis of the scalp and the associated related diseases like acne vulgaris and hidradenitis suppurativa and classify them. Patients and methods This is case series descriptive study that was carried out during the period from 2014-2021 where all patients with chronic scalp folliculitis were collected and analyzed. Full history and examination were done including the types of folliculitis whether superficial or deep, widespread or localized, scarring or none scarring and moth eaten pattern hair alopecia or not. In addition to record and evaluate the associated skin disease like acne vulgaris and hidradenitis suppurativa (HS). Results Analysis of eighty-seven patients with chronic scalp folliculitis showed that 85(97.7%) males and 2(2.29%) females, their ages ranged from 18-36 years. The duration of the disease ranged from 0.6-4 years. Three types of scalp folliculitis were recognized: The first one ,superficial folliculitis in 23(26.43%) patients, with 22(95.65%) males and one(4.34%) female while 16(69.56%) cases had also associated acne vulgaris with varying severity including two patients with HS.The second type, deep superficial folliculitis so called folliculitis decalvans were noticed in 28( 32.18% ) patients, with 27(96.42%) males and one (3.57%) female. These patients had usually single patches in 22(78.57%) cases while multiple in 4(14.28%) cases and 2(7.14%) cases presented with diffuse moth eaten alopecia. Concomitant facial acne vulgaris was seen in 2 (7.14%),truncal folliculitis in 2 (7.14%) and HS in 2(7.14%)cases. The third type so called deep cystic folliculitis(dissecting cellulitis) accounting for 36(41.37%) patients that presented with deep cystic masses in variable severity, and all cases were males. It was associated with 10 (27.77%) cases of HS involving axillae, buttocks and groins and 26 (72.22%) cases with cystic acne vulgaris of face and trunk. Conclusion Chronic scalp folliculitis is a common skin problem consisting of three variants and was commonly associated with acne vulgaris and hidradenitis suppurativa. These variants share the same etiopathogenesis and the clinical pictures hence they are parts of one spectrum. Alopecia usually a moth eaten pattern was seen in all these 3 types of scalp folliculitis but was permanent in folliculitis decalvans and non-scarring in superficial type and deep cystic folliculitis.